Immune response and endocytosis pathways are associated with the resilience against Alzheimer's disease: Genetics: Molecular genetics of AD and ADRD. (7th December 2020) - Tesi, Niccoló; Van Der Lee, Sven J.; Hulsman, Marc; Jansen, Iris E.; Stringa, Najada; van Schoor, Natasja; Scheltens, Philip; van Der Flier, Wiesje; Huisman, Martijn; Reinders, Marcel J.T.; Holstege, Henne
Abstract: Background: Developing Alzheimer's disease (AD) is influenced by multiple genetic variants that are involved in five major AD‐pathways: immune response, β‐amyloid metabolism, endocytosis, cholesterol/lipid metabolism and angiogenesis . The extent to which these pathways are involved in the resilience against AD have thus far been poorly addressed. Here, we investigated the association of each molecular mechanism with ( i ) the increased risk of AD, and ( ii ) the resilience against AD until extreme old age, by comparing pathway‐specific polygenic risk scores (pathway‐PRS). Method: We focused on 29 genetic variants identified in GWAS studies of AD to calculate a pathway‐PRS for the five major pathways involved in AD. For our pathway‐PRS, we developed an integrative framework that allows multiple genes to associate with a variant, and multiple pathways to associate with a gene. We studied the pathway‐PRSs in the Amsterdam Dementia Cohort of well‐phenotyped AD patients (N = 1, 909), Dutch population controls from the Longitudinal Aging Study Amsterdam (N = 1, 654), and our unique 100‐plus Study cohort of cognitively healthy centenarians who avoided AD (N = 293). Moreover, we estimated the contribution of each pathway to the genetic risk of AD in the general population. Result: All pathway‐PRSs (except for angiogenesis ) significantly associated with increased AD‐risk and, in the opposite direction, with resilience against AD ( p < 0.05). The pathway that contributed the most to the overall modulation of AD‐risk was β‐amyloid metabolism (29.6%), which was driven mainly by APOE ‐variants. After excluding APOE variants, all pathway‐PRSs (except for angiogenesis ) associated with increased AD‐risk ( p < 0.05), while specifically immune response ( p = 0.003) and endocytosis ( p = 2.2 × 10 −4 ) significantly associated, in the opposite direction, with resilience against AD. Indeed, the variants in these pathways were the main contributors to the overall modulation of genetic risk of AD in the general population (45.5% and 19.2%, respectively). Conclusion: The genetic variants associated with the resilience against AD indicate which pathways are involved with maintained cognitive functioning until extreme ages. Our work suggests that a favorable immune response and a maintained endocytosis pathway might be involved in neuro‐protection mechanisms of AD, which highlight the need to investigate these pathways, next to β‐amyloid metabolism .